1999
DOI: 10.1007/s100529900176
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational phase transition of fermionic matter in a general-relativistic framework

Abstract: The Thomas-Fermi model at nite temperature is extended to describe a system of self-gravitating weakly interacting massive fermions in a general-relativistic framework. The existence and properties of the gravitational phase transition in this model are investigated numerically. It is shown that, by cooling a nondegenerate gas of weakly interacting massive fermions below some critical temperature, a condensed phase emerges, consisting of quasidegenerate fermion stars. For fermion masses of 10 to 25 keV, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 30 publications
(46 reference statements)
3
66
0
2
Order By: Relevance
“…20 Equation (105) is valid at equilibrium (for a steady state). Therefore, the expressions (122) and (123) of S and N are justified only at equilibrium. However, it is shown in [51] that Eq.…”
Section: Local Thermodynamic Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…20 Equation (105) is valid at equilibrium (for a steady state). Therefore, the expressions (122) and (123) of S and N are justified only at equilibrium. However, it is shown in [51] that Eq.…”
Section: Local Thermodynamic Equilibriummentioning
confidence: 99%
“…(205) and (206) with Eq. (203) [2,123]. Remark: For the general relativistic Fermi gas at T = 0, the free energy F reduces to the binding energy E = (M − N m)c 2 .…”
Section: The Completely Degenerate Fermi Gas (Ground State)mentioning
confidence: 99%
“…is the natural length scale for fermion stars (Bilić & Viollier 1999b). We also take the same value D ol for lensing by a black hole.…”
Section: Lensing By a Schwarzschild Black Hole A Boson Star And A Fmentioning
confidence: 99%
“…Of course, the massive neutrino could be replaced by any weakly interacting fermion of the same mass. Such fermion stars could have been formed in the early Universe during a first-order gravitational phase transition (Bilić & Viollier 1997, Bilić & Viollier 1999a, Bilić & Viollier 1999b). It has recently been shown that the dark-matter concentration observed through stellar 1 Rudjer Bošković Institute, 10000 Zagreb, Croatia 2 Institute of Theoretical Physics and Astrophysics, Department of Physics, University of Cape Town, Rondebosch 7701, South Africa motion at the Galactic center , Genzel et al 1996 is consistent with a supermassive object of 2.5 × 10 6 solar masses made of self-gravitating, degenerate heavy neutrino matter (Tsiklauri & Viollier 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…1 we plot the mass of the NS as a function of the radius R. The maximum of the curve corresponds to the OV limit. The limiting values are [13] …”
Section: Pos(p2gc)004mentioning
confidence: 99%